SPUTUM SMEAR POSITIVITY AMONG PATIENTS PRESENTING TO THE DOTS CLINIC WITH CHRONIC COUGH - Kida IM; Goni BW; Ummate I; Garbati MA; Bakki B; Hammangabdo A; Yusuph H (Ntec Specialist, 2017)
Background: Cough is one of the cardinal features of Pulmonary Tuberculosis (PTB). However, even in communities with high prevalenceof TB, lung diseases other than TB appear to account for this symptom. Objective: To estimate the prevalence of sputum smear positivity among patients with TB who presented with complaints of chronic cough to the Directly Observed Therapy Short Course (DOTS) clinic at the University of Maiduguri Teaching Hospital, North Eastern Nigeria. Methodology: A cross sectional study was conducted at the University of Maiduguri Teaching Hospital (UMTH) Borno state, Northeastern Nigeria between September 2014 and January 2017. All patients (new or previously treated) who presented to the DOTS clinic of the UMTH with complaints of chronic cough and had screening for pulmonary TB using sputum smear microscopy were reviewed. Data were entered into a computer database and analyzed with SPSS version 20.0 statistical software. Results: The minimum and the maximum ages were 1 year and 85 years, respectively, and the mean age was 36.0 (SD=14.0) years. The mean age did not differ among the male and female patients (i.e.37.3 ± 14.4 vs 34.1 ± 13.2, p=0.78). The overall prevalence of sputum smear positivity for TB was 26.5%. Although majority of patients who were sputum smear positive for TB fell within the age groups 30-39 and 20-29 thus accounting for 42.6% and 28.7% respectively, however, there was no significant association between age of those with chronic cough and sputum smear positivity TB (p=0.80). Among those who were sputum smear positive, 24.3% were new cases and 2.2% were previously treated. Conclusions: This study showed a high prevalence of sputum smear positivity among suspected TB patients with complaints of chronic cough. This could be explained by the fact that the DOTS strategy has improved the case detection of PTB in this community. All patients with chronic cough should be evaluated for PTB.